Vissza: Felvidék . [Re-annex Felvidék] - Cserépy, László (Magyar Filmiroda, 1938)
Duration: 01:00:00 The war campaign of Hungary to get back Felvidék in 1938, cut off from Hungary by the peace treaties after World War I.